2010
DOI: 10.1111/j.1365-2133.2010.09629.x
|View full text |Cite
|
Sign up to set email alerts
|

Narrowband ultraviolet B course improves vitamin D balance in women in winter

Abstract: NB-UVB exposures given on seven consecutive days on different skin areas of healthy women significantly improved serum calcidiol concentration. A short low-dose NB-UVB course can improve vitamin D balance in winter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 27 publications
8
36
0
Order By: Relevance
“…The geographic location and careful seasonal timing of our study caused our subjects to have low levels of 25(OH)D at the baseline visit, although defining what constitutes deficiency is controversial. 30 We showed that 25(OH)D increases rapidly with narrowband UV-B, in agreement with previous studies 17,18,[33][34][35] We also noted that the increments of 25(OH)D became successively smaller with successive visits, an effect that has been noted before and is partly due to UV light also having a catabolic effect on the vitamin. 36 In addition, the majority of our subjects started with lower levels of CD3 1 CD4 1 CD25 hi FoxP3 1 Treg cells than those previously reported, 37,38 although proportions in different studies are difficult to compare due to variation in methodology.…”
Section: Discussionsupporting
confidence: 90%
“…The geographic location and careful seasonal timing of our study caused our subjects to have low levels of 25(OH)D at the baseline visit, although defining what constitutes deficiency is controversial. 30 We showed that 25(OH)D increases rapidly with narrowband UV-B, in agreement with previous studies 17,18,[33][34][35] We also noted that the increments of 25(OH)D became successively smaller with successive visits, an effect that has been noted before and is partly due to UV light also having a catabolic effect on the vitamin. 36 In addition, the majority of our subjects started with lower levels of CD3 1 CD4 1 CD25 hi FoxP3 1 Treg cells than those previously reported, 37,38 although proportions in different studies are difficult to compare due to variation in methodology.…”
Section: Discussionsupporting
confidence: 90%
“…Though a few studies show that NBUVB increases circulating levels of 25-hydroxy vitamin D [21, 22], there is yet no published study comparing the levels of 25(OH)D in patients of vitiligo before and after NBUVB phototherapy and correlating it with repigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Many participants demonstrated a rapid rise in [25(OH)D] during the first week, which is similar to the response to an acute dose of ultraviolet radiation exposure [25]; but distinct from the more gradual effects of other forms of exogenous vitamin D intake (e.g., oral D2 ingestion [10]). Several non-pregnant participants demonstrated peak [25(OH)D] as early as two days after supplement delivery, and there was notably wider variability in responses in the group of non-pregnant participants during the early escalation phase compared to pregnant participants.…”
Section: Discussionmentioning
confidence: 99%